English Pengenalan Terapi Non-Farmakologi pada Lansia Hipertensi di Kabupaten Klaten Jawa Tengah - safaruddin, safaruddin; Tri Yahya Christina; Lilik Sriwiyati; I Putu Juni Andika; Tunjung Sri Yulianti (LOSARI DIGITAL, 2025)
Hypertension is a chronic health problem commonly experienced by the elderly and is a major cause of cardiovascular disease. This community service activity aimed to improve elderly knowledge about hypertension management through non-pharmacological therapy in Soko Bogor, Cawas, Klaten, Central Java. The implementation methods included preparation, education, training, and evaluation stages. The intervention consisted of education on a healthy diet, physical activity, stress management, and the practice of relaxation techniques such as deep breathing and finger-hold therapy. Knowledge assessment was conducted before and after the intervention using questionnaires. The results showed a significant improvement in knowledge levels, where the “good” category increased from 10% to 70%, while the “poor” category decreased from 55% to 0%. Most participants were female (90%), indicating higher participation among women compared to men. This activity effectively enhanced the elderly’s understanding of hypertension control through non-pharmacological approaches. However, continued assistance is needed to ensure that increased knowledge translates into sustainable behavioral changes.